Documents organisation strategies of Open University Malaysia (OUM) postgraduate students - Jaspal Kaur Naranjan Singh,; Fathin Fakhriah Abdul Aziz, (2019)
Students doing research would normally download documents from the Internet on to their desktop for later use. However, these documents are not easily found again as the documents are saved indiscriminately in multiple folders on their desktop. This study aims to investigate students’ document organisation strategies on their desktop primarily. The study includes 128 Open University Malaysia (OUM) postgraduate students with personal desktop of at least 10 Portable Documents Format (PDFs) files. Personal Information Management (PIM) is an interesting research field exploring individual's activities of acquisition, organisation, maintenance, retrieval and sharing of information (Lush, 2014). Research has shown that PIM activities have an important influence on the learning processes, particularly university students engaging in many documents from various sources (Jacques & Fastrez, 2014). Data regarding their personal desktop documents were collected using survey method. The questionnaire was administered using Google Form. Two distinct categories of students’ organisation strategies were identified in this research, which are piling and filing. A discussion of these results is provided. We will then recommend personal information management organisation strategies for postgraduate students doing their research project. A proper information management organisation strategy will lead to the development of efficient information management skills of the student.